Mechanized Tools and Technovation Machinery in Palm Oil Plantations: Utilization or Rejection? - Mohd Nawi, Nur Syazwani; Md Deros, Baba; Ab Rahman, Mohd Nizam; Nordin, Norani; Sukadarin, Ezrin Hani (2015)
Palm oil is a strong contributor and one of the pillars to Malaysia’s sustainable development. The existence of various technologies and innovation (technovation) tools can help further enhance the productivity of this industry. Currently, there is a wide range of technovation or mechanized tools produced in order to replace manual tools usage. However, the majority of harvesters still continue to use manual tools. Therefore, the aim of this research is to examine the extent of implementation of technology within the organization. It highlights the types of technologies applied and also it identifies factors of the rejection of technology. A case study was conducted at three companies of oil palm plantations in Malaysia; small holders, private and government schemes. From the results, it shows that all three case study companies are using technovation tools albeit not comprehensively. Workers still remain using either the manual or traditional tools. This is due to several problems such as ergonomic issues, not to miss the cost and lack of information regarding each harvesting technological tool. To solve these problems, improvement of the human-machine connection is required during product design and product manufacturers need to play role to disseminate information and give training to the workers